PENERAPAN MODEL PEMBELAJARAN PBL PADA MATA PELAJARAN IPS UNTUK MENUMBUHKAN KEMAMPUAN BERFIKIR KRITIS SISWA KELAS IV SD NEGERI 1 MANIKYANG - Ni Made Ari Dwijayanti; I Wayan Lasmawan; I Wayan Kertih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The phenomenon observed in the field shows that many students in grade IV of SD Negeri 1 Manikyang have not demonstrated optimal critical thinking skills in Social Studies (IPS) learning. Students tend to be passive during the learning process and struggle to analyze and evaluate the available information. This study aims to explore the application of the Problem-Based Learning (PBL) model in IPS lessons and to enhance the critical thinking abilities of grade IV students at SD Negeri 1 Manikyang. The research uses a qualitative approach with a descriptive-analytic method. The subjects of the study are grade IV students of SD Negeri 1 Manikyang and the teacher who teaches IPS. Data collection techniques include literature review and direct observation of the implementation of the PBL model in teaching. Data analysis techniques are conducted through categorization, thematic analysis, and data verification to ensure the validity of the findings. The results of the study indicate that: 1) The application of the PBL model successfully increased student participation in IPS learning, with students becoming more engaged in group discussions and more confident in expressing their opinions. 2) Students' critical thinking abilities improved, as seen in their ability to analyze social issues presented to them, evaluate various possible solutions, and make appropriate decisions. 3) The PBL model also encouraged students to work collaboratively in groups, which developed their communication, cooperation, and problem-solving skills more effectively. Furthermore, students showed improvement in their ability to connect learned concepts to real-life situations.